Two Alkaloids from Bulbs of Lycoris sanguinea MAXIM. Suppress PEPCK Expression by Inhibiting the Phosphorylation of CREB. (8th July 2016) - Yun, Young Sook; Tajima, Miki; Takahashi, Shigeru; Takahashi, Yuji; Umemura, Mariko; Nakano, Haruo; Park, Hyun Sun; Inoue, Hideshi
Abstract : In the fasting state, gluconeogenesis is upregulated by glucagon. Glucagon stimulates cyclic adenosine monophosphate production, which induces the expression of key enzymes for gluconeogenesis, such as cytosolic phosphoenolpyruvate carboxykinase (PEPCK‐C), which are involved in gluconeogenesis through the protein kinase A/cAMP response element‐binding protein (CREB) pathway. Using a luciferase reporter gene assay, a methanol extract of the bulbs of Lycoris sanguinea MAXIM. var. kiushiana Makino was found to suppress cAMP‐enhanced PEPCK‐C promoter activity. In addition, two alkaloids, lycoricidine and lycoricidinol, in the extract were identified as active constituents. In forskolin‐stimulated human hepatoma cells, these alkaloids suppressed the expression of a reporter gene under the control of cAMP response element and also prevented increases in the endogenous levels of phosphorylated CREB and PEPCK mRNA expression. These results suggest that lycoricidine and lycoricidinol suppress PEPCK‐C expression by inhibiting the phosphorylation of CREB and may thus have the potential to prevent excessive gluconeogenesis in type 2 diabetes. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Lycoricidine and lycoricidinol, from methanol extract of Lycoris sanguineas uppressed the expression of a reporter gene under the control of cAMP response element and also prevented increases in the endogenous levels of phosphorylated cAMP response element‐binding protein and phosphoenolpyruvate carboxykinase mRNA expression. These results suggest that lycoricidine and lycoricidinol suppress cytosolic phosphoenolpyruvate carboxykinase expression by inhibiting the phosphorylation of cAMP response element‐binding protein and may thus have the potential to prevent excessive gluconeogenesis in type 2 diabetes.